Studies on the function and substrate permeation in ABC transporters by biomolecular simulations. - Pinto, Bárbara Palma de Abreu Caldeira (2022)
"The translocation of molecules across cell membranes often requires the participation of transmembrane proteins. The ATP Binding Cassette (ABC) transporters are one of the major class of proteins dedicated to the translocation of molecules across membranes. ABC transporters make use of ATP hydrolysis and undergo a series of large-scale conformational changes in order to carry out their function. Despite being extensively studied, some molecular details regarding their function remain undisclosed. In this thesis, the function of three relevant ABC systems, CFTR, MsbA and the Escherichia coli MalFGK2E importer, was investigated using computational methods, such as molecular dynamics simulations. The effect of the CFTR mutation F508del, responsible for cystic fibrosis, was studied in the nucleotide binding domains of the CFTR receptor. In the MsbA protein, the molecular details of nucleotide binding during the adenylate kinase cycle were investigated in collaboration with experimental groups with expertise in solid state NMR and EPR. Finally, the details of substrate translocation in the MalFGK2E importer were also researched.(...)"